2007
DOI: 10.1111/j.1572-0241.2007.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin May Reduce the Incidence and Severity of Acute Pancreatitis After ERCP

Abstract: This trial shows that rectal indomethacin given immediately before ERCP can reduce the incidence and severity of post-ERCP pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 19 publications
4
171
1
5
Order By: Relevance
“…This seems to indicate that the vulnerability of the pancreas declines with age. In this connection, the finding of Sotoudehmanesh et al [23] that the risk for post-ERCP pancreatitis is reduced in patients above the age of 60 years is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…This seems to indicate that the vulnerability of the pancreas declines with age. In this connection, the finding of Sotoudehmanesh et al [23] that the risk for post-ERCP pancreatitis is reduced in patients above the age of 60 years is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies were excluded beacuse full texts in English were not retrieved (17)(18). Finally, three studies involving a total of 1242 patients were included for data extraction (14)(15)(16). Except for one single-center study, two studies were designed as multicenter.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…After initial screening, five relevant prospective studies were identified for evaluation in details (14)(15)(16)(17)(18). Two studies were excluded beacuse full texts in English were not retrieved (17)(18).…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…There was, however, a significant protective effect among patients with inadvertent pancreatography (2% vs 19%). 132 Khoshbaten et al 133 reported that RNSAIDs significantly reduced PEP (26%-4%) in a study where pancreatography was the criterion for entry.…”
Section: Post-ercp Prophylaxismentioning
confidence: 99%